Ketika Ijazah Menentukan Demokrasi : Persepsi Masyarakat Terhadap PSU Pilkada Pesawaran - Titan Cicilia; Esti Angelita; Feby Fiola Ayu; Zahra Nur Farida; Asshifa Shalihah; Abdul Halim (CV. ITTC INDONESIA, 2025)
The Constitutional Court’s decision to mandate a revote (Pemungutan Suara Ulang, PSU) in the 2024 Pesawaran local election due to issues regarding the authenticity of one candidate's diploma has sparked significant democratic discourse. This article aims to explore the perceptions of the public and election organizers regarding the PSU and the role of educational credentials as a determining factor in democratic processes. This study adopts a qualitative case study approach through direct interviews with KPPS (Polling Station Working Committee) members and residents of Pesawaran. Findings reveal that the public generally accepted the PSU as a fair solution (MA, interview, 2025), though some expressed frustration over the political process described as